1999
DOI: 10.1046/j.1365-2044.1999.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion for Caesarean section in Malawi A study of requirements, amount given and effect on mortality

Abstract: SummaryA prospective study of mothers needing Caesarean section was undertaken to examine the need for blood transfusion, the actual number of units given and the effectiveness of blood transfusion in preventing maternal mortality. Of 3665 mothers in 22 hospitals in Malawi, 11.1% were assessed as needing a transfusion and 7.2% were transfused. There were significant differences between district and central hospitals in transfusion rates. Of those mothers who were considered to need blood, there was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…Our study has shown an overall lower transfusion rate of 0.53% compared to the published literature. Previous studies showed the transfusion rate for cesarean delivery ranging from 1.1% to 7.8% in developed countries and up to 25% in developing countries . The reason for this could be the increased proportion of elective cesarean sections by maternal request, which has led to a high cesarean rate of 54.73%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has shown an overall lower transfusion rate of 0.53% compared to the published literature. Previous studies showed the transfusion rate for cesarean delivery ranging from 1.1% to 7.8% in developed countries and up to 25% in developing countries . The reason for this could be the increased proportion of elective cesarean sections by maternal request, which has led to a high cesarean rate of 54.73%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the transfusion rate for cesarean delivery ranging from 1.1% to 7.8% in developed countries and up to 25% in developing countries. 15,[25][26][27][28][29][30][31][32][33][34] The reason for this could be the increased proportion of elective cesarean sections by maternal request, which has led to a high cesarean rate of 54.73%. As shown in other research, elective cesarean sections have less risk of requiring blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…This association may not be causal in all cases as blood loss may reflect other intraoperative problems. Fluid replacement alone, however, may improve outcome, is relatively cheap and safe,4 13 and does not carry the same risks as blood transfusion, particularly in areas of high HIV incidence. Consideringthe largely haemodynamic nature of the complications, as estimated by the anaesthetists, their own role would seem to be important in all stages of management, though the skills needed are more in basic resuscitation and follow up on the ward than in advanced knowledge of techniques in anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia, hypovolaemia, and sepsis from obstructed labour and ruptured uterus are common. Despite its importance, there are few published data on caesarean section in Africa,4 and published studies have been small5 or retrospective 6…”
Section: Introductionmentioning
confidence: 99%
“…Fenton reports that the estimated maternal mortality rate in Malawi is between 415 and 620 deaths per 100 000 maternities, some 50 times that in the UK. One in 20 women who are judged to need a transfusion of two units of blood after Caesarean section die, and this increases to one in five if three units are needed [5]. The rest of sub-Saharan Africa -with the notable exceptions of South Africa, Botswana, Namibia and Gabon -is in a similar situation.…”
mentioning
confidence: 99%